Система жанров религиозного стиля в коммуникативно-прагматическом аспекте - Ицкович, Татьяна (Studia Rossica Posnaniensia, 2019)
The present study is devoted to the systematization of genres of religious style from the point of view of communicative-pragmatic and categorical-textual aspects. The communicative-pragmatic approach is based on the components of the communication situation. The categorical-textual approach is based on the analysis of the essential features of the text. These approaches open the possibility of analyzing the text material “beyond” the language. This is important in the context of bilingualism of religious communication. Communicatively-pragmatic approach allows us to reveal the genre-forming features of Russian religious texts and their Church Slavonic counterparts.